Technology, innovation and transforming healthcare faster, smarter and together: A conversation with Dr. Rasu Shrestha - Jason Wolf (The Beryl Institute, 2019)
As part of our special issue on Innovation and Technology we had the pleasure of speaking with a visionary leader, Physician and healthcare executive, Dr. Rasu Shrestha, executive vice president and chief strategy officer at Atrium Health. In the conversation with Dr. Shrestha we were able to cover the foundational ideas of innovation and technology. We also explored its opportunities and potential pitfalls. Ultimately, we looked at the topic through the lenses of the human experience we provide in healthcare and how through a clear focus on experience and the effective integration of innovation and technology in those efforts, we can achieve the best in outcomes for all we serve in healthcare. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens